Public Health Management Readiness in Controlling the Risk of Infectious Diseases Post-Disaster - Vina Novela (Miracle Journal Get Press, 2026)
Indonesia is highly vulnerable to natural disasters, which often disrupt health systems and increase the risk of infectious disease outbreaks in the post-disaster period. Empirical quantitative evidence on the relationship between public health management preparedness and infectious disease control at the primary healthcare level remains limited. This study analyzed the association between management preparedness and post-disaster infectious disease control effectiveness in Padang Panjang, West Sumatra. A cross-sectional analytic study was conducted involving 60 health personnel engaged in post-disaster management using total sampling. Data were collected through validated structured questionnaires and supported by surveillance reports. Statistical analyses included descriptive tests, Chi-square, Spearman correlation, and multivariate logistic regression (α < 0.05). Results showed that overall preparedness was categorized as good, particularly in epidemiological surveillance, although logistical readiness was relatively weak. Infectious disease control performance was generally good in case detection, prevention coverage, and response, while disease incidence trends remained moderate. A significant positive association was found between preparedness and disease control effectiveness (p < 0.05; r = 0.462). Multivariate analysis identified surveillance systems as the strongest predictor (Adjusted OR = 4.39), followed by logistics, human resources, and intersectoral coordination. Strengthening surveillance capacity, logistics, resource distribution, and cross-sector collaboration is essential to improve sustainable post-disaster infectious disease control.